Soy food and isoflavone intake reduces the risk of cognitive impairment in elderly Japanese women - Nakamoto, Mariko; Otsuka, Rei; Nishita, Yukiko; Tange, Chikako; Tomida, Makiko; Kato, Yuki; Imai, Tomoko; Sakai, Tohru; Ando, Fujiko; Shimokata, Hiroshi (European journal of clinical nutrition, 2018)
Data were derived from the National Institute for Longevity Sciences-Longitudinal Study of Aging. Subjects comprised 403 men and 373 women aged 60-81 years at baseline who participated in the follow-up study at least once. Bean, soy product and soy isoflavone intake was assessed using a 3-day dietary record at baseline. Cognitive function was assessed by the Mini-Mental State Examination (MMSE). MMSE scores of ≤23 were used to define cognitive impairment. The relationship between bean, soy product and soy isoflavone intake and cognitive impairment was assessed using a generalized estimating equation. Multivariate-adjusted odds ratios (95% confidence intervals) for cognitive impairment with a 1 s.d. increase in total bean, total soybean and total soy isoflavone intakes were 0.48 (0.28-0.81; p = 0.006), 0.51 (0.32-0.83; p = 0.007), and 0.55 (0.32-0.93; p = 0.026), respectively, in women. Total soybean and soy isoflavone intake might decrease the risk of cognitive impairment in elderly Japanese women.